Ideational Analysis of Donald Duck’s Comic and Its Translation - Gilang Fadhilia Arvianti; Atsani Wulansari (Metathesis: Journal of English Language, Literature, and Teaching, 2019)
Translating comic is different from other different text. Most of the text that is used in the comic is dialogue or spoken language that usually can be found in the subtitle of the film. Analyzing the accurateness of the translation text can be analyzed by using Metafunction approach especially ideational analysis. In translating text into target text, not all meaning is transferring into target text. It can influence the message that is brought by the source text into target text. Through ideational analysis approach it can be analyzed although not all the meaning is transferred into target text. This becomes the reason of taking this case as an object of this research.The aims of this research are to know the meaning realization in ideational analysis approach, and to explain the impact of ideational shifting toward the equivalence of translation in target text. The method of this research uses descriptive qualitative since the data and the analysis are in the form of sentence and description. The data took from Donald Duck’s Comic and its translation version. The technique used in this research is content analysis. This research also applies criterion-based sampling that is used only to get theoretically generalization.Since this research is hoped to give significant contribution to student of English Teaching and Learning in learning ideational analysis, the function of this research is to explain the impact of ideational shifting toward the equivalence of translation in target text. Thus, this research not only can be learning material for analyzing ideational in specific text, but also in learning translation.